Sexual dimorphism of foramen magnum: a NCCT based study - Wani, Haseeb Abdul; Feroz, Imza; Dar, Saleem Mohammad; Parry, Arshed Hussain; Gojwari, Tariq Ahmad (International Journal of Clinical Trials, 2019)
Background: Radiological determination of gender relies predominantly on the skeletal radiology and assumes importance in mass natural disasters, bomb explosions, exhumations and warfare where skeletal fragmentation is common. Varied literature is present regarding the role of foramen magnum in establishing gender identification. The objective of the study was to establish normative values of cross-sectional area of foramen magnum in both genders using NCCT and try to ascertain any significant difference in cross-sectional area in the two genders which may help in gender identification. Methods: NCCT head images of 378 subjects were analysed in individuals beyond the age of skeletal immaturity. Free ROI technique using electronic calliper tool was used. The cross-sectional area of foramen magnum was automatically obtained after tracing its whole inner circumference. Results: Mean cross-sectional area of foramen magnum in females was 806.79±106.58 mm2 and was 878.33±98.42 mm2 in males. Although the cross-sectional area in males was greater than females no statistically significant difference was found. The correlation coefficient was found to be weaker (R=0.0413). Conclusions: No statistically significant difference was found between the two genders. The correlation coefficient was also weak to draw any inference about the gender of the skull on CT imaging. Further studies are needed to include other parameters like the sagittal and transverse diameters of foramen magnum in a larger sample to show importance of foramen magnum, if any, in helping gender identification of skeletal remains.